Experimental research on rubble stone masonry walls - Pinho, Fernando F. S. (2014)
HMC08 - 1st Historical Mortars Conference: Characterization, Diagnosis, Conservation, Repair and Compatibility, LNEC, Lisbon, 24-26 September 2008